Relationship between efficacy of mating disruption and gypsy moth density. Issue 1 (2nd January 2019) - Onufrieva, Ksenia S.; Hickman, Andrea D.; Leonard, Donna S.; Tobin, Patrick C.
ABSTRACT: Mating disruption tactics involve the deployment of pheromones to interfere with mate finding behaviors in insect populations. This management strategy is the dominant one used against expanding gypsy moth populations in the United States, and historically it has been assumed to be most effective against low-density populations. Operationally, mating disruption is used in areas where the season-long trap catch is <30 males/trap, however the maximum population density at which mating disruption is effective remains unknown. We analysed historical gypsy moth mating disruption treatment data from 2000 to 2010, and used this information to guide the mating disruption field studies conducted from 2012 to 2015 against artificially-created populations of various densities, from 0 to 116 males/trap/day. We observed that mating disruption tactics at a dose of 15 g AI/ha were effective against gypsy moth populations with a season-long trap catch of at least 115 males/trap. This research highlights the utility of mating disruption in higher gypsy moth densities than what is currently recommended in management programs.